Progress with new malaria vaccines - Webster Daniel; Hill Adrian V.S (The World Health Organization, 2003)
Malaria is a parasitic disease of major global health significance that causes an estimated 2.7 million deaths each year. In this review we describe the burden of malaria and discuss the complicated life cycle of Plasmodium falciparum, the parasite responsible for most of the deaths from the disease, before reviewing the evidence that suggests that a malaria vaccine is an attainable goal. Significant advances have recently been made in vaccine science, and we review new vaccine technologies and the evaluation of candidate malaria vaccines in human and animal studies worldwide. Finally, we discuss the prospects for a malaria vaccine and the need for iterative vaccine development as well as potential hurdles to be overcome.